We are playing relatives a survey of Malay writing - Maier, Hendrik M.J.; Institute of Southeast Asian Studies (Singapore Institute of Southeast Asian Studies, 2004)
We are playing relatives offers a comprehensive survey of literature writing in the malay language. It starts with the playful evocations of language and reality in the Hikayat hang Tuah, a work that circulated on the Malay Peninsula in the eighteenth century, and follows the Malay literary impulse up to the beginning of the twenty-first century, a time when the dominant notions of Malay literature seem to fade away in the cyberspace created on the island of Java, and the Hikayat Hang Tuah's play and dance on the sounds of Malay words seem to be infused with a new vitality.--Cover
I. We are playing relatives: a survey of Malay writing -- On the emergence of 'language' -- On reality and purity -- On Kacukan -- The rise of Bahasa Indonesia -- The rise of Bahasa Malaysia -- On confusion -- On dichotomies -- On position and perspective -- II. A vade mecum of Malay writing: the fragrant flowers of the tale of Hang Tuah -- On Malay reading and writing -- The voice of writing -- The dangers of writing -- On speaking and writing -- The garden of writing -- Days of yore -- A short survey of Malay writing -- on regeneration -- On system and standard -- On lists, catalogues, and surveys -- Hikayat Hang Tuah -- On history, literature, poetics, ethics, and farragos -- A eulogy of writing -- On Java, Islam, and commoners -- A vade mecum -- On commemoration -- III. Repetitions and beginnings: Muhammad Bakir and his Hikayat Sempurna Jaya -- A new edition -- The rise of print -- on Muhammad Bakir and his work -- On tradition and modernity -- A summary -- The shadow of shadow play -- Puppeteer, dalang, composer -- On revenge and desire -- Batavia: boredom, crime, adn fear -- On translation -- On translation -- On novelty -- On Njai Dasima -- They walk to the west, they walk to the east -- Moving on the borderline -- IV. 'Yuck! Europeesche beschaving!': Mas Marco Kartodikromos's students Hidyo -- 'A newspaper is a sharp weapon' -- The world is in motion -- The law -- A writing career -- About student green -- To improve the aspects that are not good -- Good and bad -- Tendenz -- On bad memory and ignorance -- On segmentation and fragmentation -- The re-emergence of Mas Marco Kartodikromo -- V. Malay dreams: Ahmad bin Muhammad Rashid Talu and his friends -- The peninsula, the islands -- On Abdullah bin Abdul Kadir -- The rise of Balai Poestaka -- Writing life on the Peninsula -- On wise friends -- A network of friends -- Syed Syeikh bin Ahmad al-Hadi -- Artists and artisans, authors and writers -- Ont he poverty of Malays -- On living examples -- Ahmad bin Muhammad Rashid Talu and his pen -- On Malay realism -- Round again -- Of dreams and anger -- On final dreams and never-never lands -- VI. A eulogy of mechanical sounds: Armijn PAne and his shackles -- 'Kort overzicht' -- On Balai Poestaka: co and non-co -- A tale of anger and frustration -- East and West: the Polemik -- The shackles of anxiety -- on Poedjangga Baro and soekma -- Triangles: the music of interpretation -- On voices -- On voice, sound, and music -- Eulogies -- The open door -- VII. Sparks of love and misery: Hamka and Tenggelamya kapal van der Wijck -- On sorrow -- On reminiscences -- On art -- Wandering is of vert great use -- On the beautiful emotions of Islam -- On master A. lover and other tales -- A genealogy of Islam writers -- On tears and tales -- Once again: playing relatives -- A summary -- On personal love and misery -- On adat and tradition -- A eulogy of writing -- On love, deferral, and death -- Plagiarism -- On Islamic literature -- The sky is darkening -- The basis of my authorship is love -- VIII. The notes of a lonely man: Pramoedya Ananta Toer in the world of human beings -- On Buru: language and the new order -- On a manifest -- On realism and demise -- Literature during the new order -- A beautiful world covered by hell: the visibility of sastra pop -- On 'lonely songs' and the 'cultural hurricane' -- On censorship -- Lonely songs: sastra as avant-garde -- The work of Buru -- The quartet -- On Minke, Tirto and Pramoedya -- on novels and happy endings -- Polyvocality and plays -- Tempo doeloe and the redefinition of sastra -- On dialogues and plays -- On fluidity and homogenization -- IX. In search of what is gone: adventures in Cyberia -- Insular developments around 2000 -- The soto sellers of kalam -- Writing, literature, sastra -- The vitality of sastra Indonesia -- Of evanescence and elusiveness -- Still playing -- Dancing in Cyberia -- Cyberia and print.
Includes bibliographical references (pages [507]-526) and index.
Keywords: Malay literature -- History and criticism